LEARNING FUN DURING THE COVID-19 PANDEMIC: PHENOMENOLOGICAL RESEARCH BASED ON THE PERSPECTIVE OF ELEMENTARY SCHOOL STUDENTSPEMBELAJARAN - Ani Rostiani; Julia Julia (Universitas Pendidikan Indonesia, 2023)
This study aims to dig up information about fun learning during the Covid-19 pandemic. This study is focused on analyzing the perspectives of high school elementary school students regarding fun learning during the Covid-19 pandemic. The method used is qualitative with a phenomenological design, data collected from a qualitative approach by conducting interviews and distributing questionnaires. The participants in this study were 19 fourth, fifth, and sixth grade elementary school students. The results of data collection were analyzed to form several themes. The results of the study show the importance of the skills and personality of the teacher in teaching because it greatly influences students' understanding and passion for learning. The nature and attitude shown by the teacher to students greatly influences learning, how the teacher conveys the material, chooses learning methods, and chooses learning media can attract students to enjoy learning. The role of parents is also one of the supporting factors for the creation of fun learning during the pandemic. It is very important to collaborate between teachers and parents to achieve learning goals so that they can create fun learning during the Covid-19 pandemic.